Nexus of Risk-taking Behavior, Capitalization, and Profitability of Chinese Banks: Evidence from Panel Threshold Regression - Perhiar, Shumaila Meer; Khan, Muhammad Kamran; Khan, Muhammad Asad; Anwar, Muhammad Mudassar; Shah, Syed Arshad Ali; khan, Azhar (The journal of contemporary issues in business and government, 2020)
The study is based on the nexus of capitalization, risk-taking, and profitability of 187 commercial banks of the People‟s Republic of China (P.R.C) around the years 2011 to 2018. Research regulates a single threshold level for bank size and reviews the nonlinear correlation of capitalization, return on assets, and return on equity with the use of pmodels like panel ordinary least square (POLS), fixed effect (FE), and panel threshold regression (PTR). The value of threshold amounts to approximately 1,371,44 USD 1000 of total assets above this level market capitalization positively affect bank performance. The magnitude of capitalization declines from 3.14% to 0.65% for return on assets and from 21.9% to 1.56% for return on equity for banks is excessively larger after crossing the threshold level in the China banking sector.